CHILD ABUSE AND NEGLECT – A CASE SERIES (Journal of Forensic Medicine & Toxicology, 2022)
Child abuse and neglect are serious problems prevailing all over the world which may seriously damage the psychological state of the child permanently. Child maltreatment appears to affect men and women differently, with larger effects for women than men. It can happen anywhere – at home or elsewhere. It can occur in all cultures, countries and economic classes. Usually, a member of the family is involved rather than a stranger. Assessment and treatment of such maltreated children generally requires more time and multimodal approach from knowledgeable clinicians along with support of legal and child protections services. Here we present four cases of child abuse involving physical, sexual, emotional or neglect in child care.
Keywords: Child abuse; Child neglect; Physical abuse; Sexual abuse